2015
DOI: 10.1371/journal.pone.0122768
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effects of Voluntary Running on Metabolic Syndrome-Related Disorders in Non-Obese Hereditary Hypertriacylglycerolemic Rats

Abstract: While metabolic syndrome is often associated with obesity, 25% of humans suffering from it are not obese and the effect of physical activity remains unclear in such cases. Therefore, we used hereditary hypertriaclyglycerolemic (HHTg) rats as a unique model for studying the effect of spontaneous physical activity [voluntary running (VR)] on metabolic syndrome-related disorders, such as dyslipidemia, in non-obese subjects. Adult HHTg males were fed standard (CD) or high-sucrose (HSD) diets ad libitum for four we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…Cardiac hypotrophy could be related to the fact that hypertriglyceridemia and metabolic syndrome are associated with increased lipid accumulation in nonadipose tissues. Ectopically stored lipids and their metabolites (diacylglycerols, ceramides, and fatty acyl-CoAs) in the liver, heart, muscles, and kidney lead to lipotoxicity, which may result in tissue injury [ 17 , 18 ]. We found increased levels of kidney and liver injury markers, such as alanine-aminotransferase, which also demonstrates myocardial damage [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac hypotrophy could be related to the fact that hypertriglyceridemia and metabolic syndrome are associated with increased lipid accumulation in nonadipose tissues. Ectopically stored lipids and their metabolites (diacylglycerols, ceramides, and fatty acyl-CoAs) in the liver, heart, muscles, and kidney lead to lipotoxicity, which may result in tissue injury [ 17 , 18 ]. We found increased levels of kidney and liver injury markers, such as alanine-aminotransferase, which also demonstrates myocardial damage [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the paucity of lipidomics-focused studies on human liver biopsies in the NAFLD context, data from studies in rodent NAFLD models, which are more abundant, may provide the best information on sphingolipids in NAFLD. Among studies where NAFLD sphingolipidomes can be compared to controls, there are to date about nine performed in murine models [10, 11, 17, 2833], three on rat [3436], and one on rabbit [37]. Of the mouse studies, eight presented sphingolipidomics contrasting a control diet with those on a NAFLD-inducing diet, and one utilized the leptin receptor deficient ob/ob mouse [33].…”
Section: Sphingolipid Profiling In Nafldmentioning
confidence: 99%
“…Within cells, proteins are under constant surveillance by the proteolytic systems that promote the degradation of proteins damaged by highly reactive molecules, thus operating a protein quality control and preserving muscle health (Kaushik and Cuervo, ). Interestingly, reduced oxidative stress (Škop et al, ) and increase in proteasome‐mediated proteolysis has been found following both acute (Pasiakos et al, ) and chronic endurance exercise (Cunha et al, ) in healthy conditions.…”
Section: Introductionmentioning
confidence: 99%